A new species of Neurothaumasia Le Marchand (Lepidoptera, Tineidae) from Crete, Greece - Huemer, Peter; Aarvik, Leif; Berggren, Kai (Zootaxa, 2023)
A new species of fungus moths (Tineidae), Neurothaumasia cretica sp. nov., is described from specimens collected on Crete isl. (Greece). It differs from congeneric taxa by the characteristic black and white forewing pattern which is only shared with N. fasciata Petersen, 1959 from the Middle East, and the widespread western Palaearctic N. ankerella (Mann, 1867). However, the new species differs strongly from the former by several characters of male and female genitalia, and from the latter species particularly from external appearance and by the highly divergent DNA barcode (cytochrome c-oxidase subunit 1) (unknown for N. fasciata). Adult and genitalia of N. cretica sp. nov. and the only similar European species N. ankerella are shown for comparison. Finally, a complete checklist of the genus is added.